Synthesis and Application of Photoactive Nanomaterials for Antimicrobial and Catalytic Activity - Bourgonje, Connor (Université d'Ottawa | University of Ottawa, 2025)
In this work we sought to investigate the fascinating and powerful interactions between light and metal nanoparticles of silver (AgNPs) and palladium (PdNPs) to enhance their applications in photobiology and catalysis. This work begins with the synthesis of citrate capped silver NPs using in-flow irradiation of various Norrish Type-1 photoinitiators with AgNO3 to generate AgNP “seeds” rapidly, and at relatively large scale. Using these seeds, we can take advantage of their high sensitivity to light to further drive the growth of these small AgNPs into larger, more complex structures such as triangles and decahedra without having to add bulky surfactants or polymers. In this approach, we can control nanoparticle shape using different wavelengths of LED illumination, while adjusting citrate concentration can allow for the fine tuning of AgNP absorbance throughout the visible spectrum, and into the NIR region. Using our light-generated AgNPs, we observe potent light-activated antibacterial effects when irradiating the NPs with light wavelengths corresponding to their plasmonic absorbance. These particles are able to totally wipe out bacterial cultures in batch at high bacterial concentrations at AgNP concentrations as low as 10 ppm. These highly antibacterial NPs can also be fixed to a heterogenous support, glass wool (AgNPs@GW), to act as a heterogenous antibacterial agent, effectively killing bacteria under white light irradiation for effective in-flow treatment of bacteria contaminated water. We show that the antibacterial effects from these particles may be derived from a combined light-activated heating effect, along with light-induced reactive oxygen species (ROS) generation. Applying these same lessons to industrially relevant reactions, in our final chapter we utilize the same versatile support, glass wool, to fix PdNPs, making an effective heterogenous nitro-to-amine photocatalyst. Using a broad range of characterization methods, we demonstrate the effectiveness of high-resolution light microscopy techniques (confocal, TIRF, FLIM) at visualizing the catalytic sites on PdNP coated GW fibres. Under these conditions, we show that Pd on GW is a stable and robust catalyst for the nitro-to-amine reaction, showing little catalyst migration or loss of activity, even after several hours on continuous flow. This work demonstrates the utilization of visible and NIR irradiation to control nanoparticle synthesis, enhance antibacterial activity, develop in-flow water treatments, and drive flow-photoreactors. Altogether, this thesis aims to demonstrate the enhanced capabilities of materials when they interact with light, effectively enhancing their already fascinating properties.
Keywords: Photochemistry; Nanomaterials; Silver Nanoparticles; Antimicrobial materials; Palladium Nanoparticles; Single Molecule Microscopy